The normal transverse mesocolon and involvement of the mesocolon in acute pancreatitis: an MRI study. - Xiao Xiao Chi; Xiao Ming Zhang; Tian Wu Chen; Xiao Hua Huang; Lin Yang; Wei Tang; Bo Xiao (PLoS ONE)
Objective To study the MRI findings of the normal transverse mesocolon and the involvement of the mesocolon in acute pancreatitis (AP) as well as the relationship between the involvement of the mesocolon and the severity of AP. Materials and methods Forty patients without pancreatic disorders were retrospectively analyzed to observe the normal transverse mesocolon using MRI; 210 patients with AP confirmed by clinical and laboratory tests were retrospectively analyzed using MRI to observe transverse-mesocolon involvement (TMI). The severity of TMI was recorded as zero points (no abnormalities and transverse-mesocolon vessel involvement), one point (linear and patchy signal in the transverse mesocolon) or two points (transverse-mesocolon effusion). The AP severity was graded by the MRI severity index (MRSI) and the Acute Physiology And Chronic Healthy Evaluation II (APACHE II) scoring system. The correlations of TMI with MRSI and APACHE-II were analyzed. Results In a normal transverse mesocolon, the display rates of the middle colic artery, the middle colic vein and the gastrocolic trunk on MRI were 95.0%, 82.5% and 100.0%, respectively. Of the 210 patients with AP, 130 patients (61.9%) had TMI. According to the TMI grading, 40%, 39% and 20% of the patients were graded at zero, one and two points, respectively. TMI was strongly correlated with the MRSI score (r = 0.759, P = 0.000) and the APACHE-II score (r = 0.384, P = 0.000). Conclusion MRI could be used to visualize transverse-mesocolon involvement. The severity of TMI could reflect that of AP in the clinical setting and imaging. TMI might be a supplementary indicator of the severity of AP.